CHANGES IN ENJOYMENT OF PHYSICAL ACTIVITY, ACTUAL AND PERCEIVED PHYSICAL ABILITIES IN PRIMARY SCHOOL CHILDREN (Fiep Bulletin - online, 2014)
Enjoyment of physical activity (PA), actual and perceived physical abilities are important factors in promoting active lifestyles and regular PA among children [1,2], but little research has investigated these relationships over time. The aim of the study was to examine changes in these variables in primary school children involved in an additional physical education lessons program (2 times week-1). Tests involving the standing long jump, 1 kg medicine-ball throw, 10 × 4m shuttle-run, basketball throw and 20m sprint[3,4] were administered before (T0) and after (T1) a 4-month intervention in 178 boys and 184 girls aged 8 to 10 years. Enjoyment and levels of PA were assessed using the Physical Activity Enjoyment Scale (PACES )[1] and the Physical Activity Questionnaire for Older Children (PAQ-C)[5], respectively. Individuals’ perceptions of strength, speed and agility were measured using the Perceived Physical Ability Scale for Children (PPAS_C)[6]. Significant time effects were found, with participants reporting higher PA (p
Keywords: enjoyment; perceived physical ability; physical activity; physical education; physical fitness.